The Impact Of The Covid-19 Pandemic on ‘Right To Health’. Implications of Free Health-Care Vs. Health-Care Insurance Schemes: A Comparative Analysis - Amarasinghe, Kusal (Junior Bar Association, Sri Lanka, 2020)
The COVID-19 pandemic has created an unprecedented disruption for the entire civilization on a global scale. On 9th of April 2020, UN General Secretary, António Guterres stated the Security Council that the world faces its gravest threat since the founding of the United Nations Organization. While the deadly epidemic has horrendously spread from a single case in China to a global pandemic, the death toll has exceeded one and half million around the world. The economic costs of the pandemic will be larger than the damage caused by the economic crisis in 2008. While the pandemic is rapidly spreading globally, a new discourse on the ‘Right to Health’ has emerged more prominently. Generally, there are two fundamental arguments on ‘Healthcare’. The first one depends on the neo-liberal approach which considers the health-care is not a social right. Therefore, health-care may not be guaranteed as a Human Right. The concept of health-care insurance schemes mainly based on this neo-liberal argument. The second argument is that health-care, which includes the ‘Right to Healthcare’ and social and other underlying determinants of health, should be protected as a ‘Basic Human Right’. This argument is the basis for the concept of universal free health care. The main objective of this study is to explore the contradiction between the implications of free healthcare and healthcare insurance schemes with a comparative analysis to find out what is the most appropriate healthcare model to protect the Right to Health as a Human Right.
Keywords: Right to Health; COVID-19